Observational study on the use of Neem and Hypericum oils in non-hospitalized COVID-19 patients - Fiorella Carnevali; Giuseppe Noschese (Zenodo, 2020)
This report describes the efforts of a healthcare worker in the Campania region badly affected by COVID-19 to repurpose a pre-existing medical device with the intent to benefit patients and ease pressure on local hospitals. Materials and Methods: The study consist of self-reported symptoms, collected over a two month period on an unscreened cohort of patients in a wide age range presenting mild to moderate symptoms consistent with COVID-19, treated with a spray containing Neem and Hypericum (1 Primary Wound Dressing, Kerecis, Iceland) with directions for oral and nasal self-administration for two weeks. The severity and nature of the symptoms were captured on a scale of 0 (not present) to 3 (serious). After beginning treatment, the patients were followed up by phone call or visits and their self-reported symptoms were documented in the form of a score. Results: Out of the 64 treated patients, 63 had recovered eventually as of May 2020 and none of them had received hospital care or died, only 29 patients gave consent for their data to be presented here. Due to limited resources, only 4 out of these 29 patients were screened for SARS-CoV-2 and all tested positive. All have recovered fully, except for one 25-year-old female who still has a low-grade fever after 2 months of illness. No side effects or discomfort were reported from using the spray. Patients who started treatment early after the onset of symptoms had a much shorter course of the disease than those who started treatment later: the average time to recovery was 17.9 ± 9.8 days (range 5-38 days). Discussion: The spray described here contains 50% neem oil and 50% Hypericum (St. John´s Wort). The antiviral properties of these two spray constituents have been previously reported, including against another related Corona virus, the Infectious bronchitis virus (IBV). Direct comparison to the recovery trajectory of other Neapolitan COVID-19 patients is impossible as most mildly symptomatic patients were never screened. However, due to the nature of the outbreak ...